2013
DOI: 10.1542/peds.2012-0376
|View full text |Cite
|
Sign up to set email alerts
|

Complete Remission Following Decitabine/Dendritic Cell Vaccine for Relapsed Neuroblastoma

Abstract: Patients with relapsed stage 4 neuroblastoma have an extremely poor long-term prognosis, making the investigation of new agents of interest. We report the outcome of the first patient treated in a phase 1 study for relapsed neuroblastoma, using the chemotherapy agent decitabine to upregulate cancer testis antigen expression, followed by a dendritic cell vaccine targeting the cancer testis antigens MAGE-A1, MAGE-A3, and NY-ESO-1. Our patient had persistent tumor in his bone marrow after completion of standard t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 25 publications
0
22
0
1
Order By: Relevance
“…Thus, combined AZA+RA treatment shows efficacy in NB cells with different combinations of severe genetic aberrations associated with high-risk NB: 1p36 AZA is already in clinical use for treatment of myelodysplasive syndrome (11) and in several clinical trials for different types of tumors (33). In a phase I case study, a patient who suffered from relapsed stage 4 NB received AZA treatment combined with dendritic cell vaccine, which resulted in complete remission (34). In addition, clinical studies combining AZA with RA for treating Acute Myeloid Leukemia are underway (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, combined AZA+RA treatment shows efficacy in NB cells with different combinations of severe genetic aberrations associated with high-risk NB: 1p36 AZA is already in clinical use for treatment of myelodysplasive syndrome (11) and in several clinical trials for different types of tumors (33). In a phase I case study, a patient who suffered from relapsed stage 4 NB received AZA treatment combined with dendritic cell vaccine, which resulted in complete remission (34). In addition, clinical studies combining AZA with RA for treating Acute Myeloid Leukemia are underway (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Further analyses have revealed that mismatches for natural killer (NK) cell KIR/KIRligand genotypes and polymorphisms in the Fcγ receptor have also been associated with better responses to anti-GD2 immunotherapy [142,143]. With the significant side effects and known limitations of anti-GD2 antibody immunotherapy, many other immunologic approaches have been evaluated recently, including therapy with immunomodulatory CTLA4 checkpoint inhibitors [144], antitumor vaccines [145,146], and cell-based immunotherapy using either NK cells [147] or anti-GD2 targeted autologous T cells [148], which have been shown to have antitumor activity, including activity in cases with measurable disease [149,150]. Next-generation chimeric antigen receptor T cells, in which the constructs will include costimulatory domains to activate the T cell, are currently being developed [151].…”
Section: Treatment -Relapsed and Refractory Neuroblastomamentioning
confidence: 99%
“…A DNA vaccine encoding calreticulin (CRT) linked to human papillomavirus type 16 E7 antigen (CRT/E7) combined with decitabine increased CRT/E7 expression, leading to enhanced E7-specific CD8 + T-cell response as well as the anti-tumor effects of CRT/E7 vaccine [111]. A Phase I trial for relapsed neuroblastoma used decitabine to upregulate CTA expression followed by a dendritic cell vaccine targeting the MAGE-A1/3 and NY-ESO-1 [112]. Although downregulation of HLA class I/II molecules was observed in neuroblastoma [113], a mixture of peptides derived from each full-length antigen was used.…”
Section: Combination Of Immunotherapy and Decitabinementioning
confidence: 99%
“…Currently, decitabine as an immunemodulator is combined with vaccine or adoptive cell therapy in some clinical trials. Decitabine combined with vaccine targeting some CTAs such as NY-ESO-1 [115], MAGE-1 [116] and MAGE-A1 [112] are being carried out or complete. These trials may utilize the effects of decitabine in inducing the expression of CTAs and HLA molecules before vaccine could overcome immune evasion of cancer cells, contributing to enhancing CTA-specific immune responses in malignant patients.…”
Section: Combination Of Immunotherapy and Decitabinementioning
confidence: 99%